La gestión del markenting y el posicionamiento en el mercado de la empresa panificadora Bellavista. - López Panata, Caroline Mishell (2025)
The present degree thesis has as its theme: “MARKETING MANAGEMENT AND MARKET POSITIONING OF THE BELLAVISTA BAKERY COMPANY”, for its development we started from the definition of the problem, then we defined the objectives and the justifications as support, the bibliographical consultation of the variables was made, the operability of the variables was defined, establishing that it is a research of the inductive-deductive method. The techniques used for data collection are the survey applied to workers and a legally representative highway where the problem was visible. Also, a market survey was conducted to determine consumer trends and what are the means that can be used in a marketing plan Afterwards, the results were presented and it was determined that it is necessary to have that document because it is recognized that it is not previously evaluated in the marketing processes and that there has not been an adequate follow-up of it, it has been intended to make promotions and advertising but without evaluating its effectiveness related to this has a loss in the clientele and in the income that has been reported in the problem being necessary the creation of a marketing plan where the activities, strategies and responsible were defined in order to achieve better results and the positioning of the brand